Theorical analysis of a monolithic all-active three-section semiconductor laser - Bouchene, Mohammed Mehdi; Hamdi, Rachid; Zou, Qin (Photonics Letters of Poland, 2017)
We propose a novel semiconductor laser structure. It is composed of three cascaded active sections: a Fabry-Pérot laser section sandwiched between two gain-coupled distributed feedback (DFB) laser sections. We have modeled this multi-section structure. The simulation results show that compared with index- and gain-coupled DFB lasers, a significant reduction in the longitudinal spatial-hole burning can be obtained with the proposed device, and that this leads to a stable single longitudinal mode operation at relatively high optical power with a SMSR exceeding 56dB. Full Text: PDF References L.A. Coldren, "Monolithic tunable diode lasers", IEEE J. Select. Topics Quant. Electron. 6, 988 (2000) CrossRef O. Kjebon, R. Schatz, S. Lourdudoss, S. Nilsson, B. Stalnacke, L. Backbom, "30 GHz direct modulation bandwidth in detuned loaded InGaAsP DBR lasers at 1.55 [micro sign]m wavelength", Electron. Lett. 33(6), 488 (1997). CrossRef N. Kim, J. Shin, E. Sim, C.W. Lee, D.-S. Yee, M.Y. Jeon, Y. Jang, K.H. Park, "Monolithic dual-mode distributed feedback semiconductor laser for tunable continuous-wave terahertz generation", Opt. Expr. 17(16), 13851 (2009). CrossRef M.J. Wallace, R. ORreilly Meehan, R.R Enright, F. Bello, D. Mccloskey, B. Barabadi, E.N. Wang, J.F. Donegan, "Athermal operation of multi-section slotted tunable lasers", Opt. Expr. 25(13), 14426 (2017). CrossRef J.E. Carroll, J.E.A. Whiteaway, R.G.S. Plumb, "Distributed Feedback Semiconductor Lasers", Distributed feedback semiconductor lasers (IEE and SPIE, 1998). CrossRef H. Ghafour-Shiraz, Distributed Feedback Laser Diodes and Optical Tunable Filters (Wiley, 2003). CrossRef D.D. Marcenac, Ph.D dissertation (University of Cambridge, 1993). DirectLink L.M. Zhang, J.E. Carroll, C. Tsang, "Dynamic response of the gain-coupled DFB laser", IEEE J. Quant. Electr. 29, 1722 (1993). CrossRef W. Li, W.-P. Huang, X. Li, J. Hong, "Multiwavelength gain-coupled DFB laser cascade: design modeling and simulation", IEEE J. Quant. Electro. 36(10), 1110 (2000). CrossRef B.M. Mehdi, H. Rachid, in Proc. 3rd Intern. Conf. on Embedded Systems in Telecomm. and Instrument., Annaba, Algeria (2016). DirectLink C. Henry, "Theory of the linewidth of semiconductor lasers", IEEE J.Quant. Electr. QE-18, 259 (1982). CrossRef K. Takaki, T. Kise, K. Maruyama, N. Yamanaka, M. Funabashi, A. Kasukawa, "Reduced linewidth re-broadening by suppressing longitudinal spatial hole burning in high-power 1.55-/spl mu/m continuous-wave distributed-feedback (CW-DFB) laser diodes", IEEE J. Quant. Electr. 39, 1060 (2003) CrossRef